2021
DOI: 10.1108/mip-07-2020-0304
|View full text |Cite
|
Sign up to set email alerts
|

Impact of consumer innovativeness on really new product adoption

Abstract: PurposeThe purpose of this study is to explore consumer innovativeness as a personality trait and addresses the hedonic, social, cognitive and functional motivational elements that lie behind consumer innovativeness. It explores the weak relationship between consumer innovativeness and really new product (novel innovation) adoption and challenges the classic relationship between consumer learning, attitude and intention.Design/methodology/approachThis study adopts a quantitative approach, gathering survey data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 99 publications
(165 reference statements)
1
31
1
1
Order By: Relevance
“…Regarding the adoption of high-technology products and services, previous studies often addressed innovativeness as a single dimension, whereas recent research suggested a multidimensional construct [38][39][40]. These studies classified multiple types of innovativeness by referring to the four-dimensional motivated consumer innovativeness proposed by Vandecasteele and Geuens [20].…”
Section: Antecedents Of the Dual Factor: Motivated Innovativeness And Previous Privacy-invasion Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the adoption of high-technology products and services, previous studies often addressed innovativeness as a single dimension, whereas recent research suggested a multidimensional construct [38][39][40]. These studies classified multiple types of innovativeness by referring to the four-dimensional motivated consumer innovativeness proposed by Vandecasteele and Geuens [20].…”
Section: Antecedents Of the Dual Factor: Motivated Innovativeness And Previous Privacy-invasion Experiencementioning
confidence: 99%
“…Thus, individuals who are motivated with higher innovativeness are more positively aware of the personalization provided by IoT services. Innovativeness can be classified into four dimensions: cognitive, functional, hedonic, and social [20,[38][39][40].…”
Section: Hypothesis 1 (H1) Personalization Positively Affects the Intention To Use Iot Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 illustrates the latest findings on the same. ,1975;Midgley & Dowling, 1978;Hirschman,1980;Venkatraman,1991;Agarwal & Prasad,1998;Roehrich, 2004;Lu et al,2005;Dobre et al, 2009;Xu & Gupta, 2009;Park & Kim, 2010;Bouwman et al,2014;Lu ,2014;Rahman et al,2014;Thakur, Angriawan & Summey,2016;Truong et al,2017;Krey et al,2019;Klein,Horak, Li & Bacouel ,2019;Esfahani & Reynolds ,2021) Traits influenced by culture (McCrae & Costa ,1997;McCrae & Costa ,1998;Church ,2000;Hofstede & McCrae ,2004;Fleeson & Jayawickreme ,2015) Also, as stated in many definitions; culture influences society by its values (Deshpande et al,1993;Yeniyurt & Townsend, 2003;Kirkman et al,2006;Geertz, 1973;Hofstede & McCrae, 2004;Benedict, 1934;Yaprak, 2008;Gamage & Wickramasinghe,2012;Maitland, 1999). So, it is important to study the value structure when understanding IN, its significance to the customer's cognitive structure, and personal values (Steenkamp et al, 1999).…”
Section: Theoretical Gapmentioning
confidence: 99%
“…Tüketici yenilikçiliğine etki eden çeşitli demografik faktörler geçmişten günümüze pek çok araştırmacı tarafından ele alınmış ve zaman içinde farklı sonuçlarla karşılaşılmıştır (Esfahani ve Reynolds, 2021;Triwijayati, vd., 2020). Buna göre genç, eğitim seviyesi yüksek, bekar, kişisel geliri yüksek olan bireylerin diğer tüketicilere kıyasla yeniliklere daha kolay adapte oldukları, yenilikçi tutum ve davranışlara daha eğilimlidir (Baumgarten, 1975;Midgley ve Dowling, 1978;Venkatraman, 1991;Midgley ve Dowling 1993;Fell, vd., 2003;Tsu Wee, 2003).…”
Section: Yenilik Ve Tüketici Yenilikçiliği Kavramlarıunclassified